Perspektif Hukum Persaingan Usaha terhadap Diskriminasi Harga Penjualan Barang pada Pasar Kaget dan Pasar Tradisional - Yetti Yetti; Yelia Natassa Winstar; Miftahul Haq (Magister Kenotariatan, Universitas Jambi, 2021)
The problem in this research, how is the regulation, the selling price of goods in shock market in traditional markets, and the perspective of business competition law. and the legal consequences caused by these prices. The purpose of research on how the flight system, the sale price of goods in shock markets and traditional markets and the legal prices caused by these nationalities. The method to achieve the goal is to conduct sociological law research, which is to see the implementation of laws in society. The results of the national research that took place in Pasar Kaget with traditional markets on basic food items. Small entrepreneurs who are in traditional markets feel disadvantaged by market traders who are shocked because market traders are surprised to give cheaper prices to consumers for the same goods. Thus the traditional market has more consumers. This happens because the law of business competition gives privileges to small traders to exercise a monopoly, which in this case is an airline. The legal consequence of the existence of a shock market is that because its establishment is not in accordance with criteria such as traditional markets, it is difficult to carry out supervision by the relevant officials, even though between traders and the principles of symbiotic mutualism. It is recommended that the government amend this law because with the freedom of small entrepreneurs that are detrimental to other small rulers.